Efficacy of laser obliteration with limited excision of pilonidal sinus - Erekle Gratiashvili; Lali Akhmeteli; Teimuraz Ivanishvili; Salome Kobadze; Nodar Giorgadze (Journal of International Medical Research, 2024)
Objective This study was performed to compare the effectiveness of laser obliteration with limited excision (LOLE) versus wide excision (WE) of the pilonidal sinus. Methods A prospective, cross-sectional observational study of 152 patients with chronic pilonidal sinus disease was performed from September 2019 to September 2022. Of the 152 patients, 76 underwent LOLE and 76 underwent WE. The main evaluation criteria were complete wound healing, recurrence, and the complication rate. Results Complete healing was achieved in 74 (97.4%) patients in the LOLE group and 76 (100%) patients in the WE group. The duration of wound healing was significantly shorter in the LOLE group than in the WE group (6.5 ± 2.4 vs. 14.5 ± 2.6 weeks, respectively). Recurrence developed in six (7.9%) patients in the LOLE group and one (1.3%) patient in the WE group, with no significant difference. Conclusion According to our study and the data available in the literature, laser surgery should be included in the guidelines for the treatment and management of pilonidal disease.